Acordo, reflexão e filosofia - uma análise a partir de Wittgenstein - Martins, Clélia Aparecida [UNESP] (My University, 2010)
Within the Wittgensteinian approach, the ideal of exactness, disconnected from concrete situations of language use, does not make any sense. Such an approach takes into account every and any kind of intersubjective communication, inasmuch as it is based on a previous agreement concerning the use of language and the interpretation of the world linked to it. This paper, throughout its three parts, seeks to understand this agreement, and evaluates whether or not philosophy plays a role in relation to it. To start with, the obstacles to such an agreement will be considered, namely, solipsism and private, subjective language. In the following stage, the intention is to indicate that the rupture from the subjectivist conception of language allows Wittgenstein to visualize another subject, the one incorporated by the community. From then on, the question is to verify whether reflectivity is possible in the ambit of a linguistic community or not, since the objectivity of concepts is not sought within knowledge, but within forms of life. In the third and last part, we will point to the language game metaphor correlative to the meaning emerging from the flow of life, of thought, and of culture and see how philosophy can represent a significant activity in the search for understanding that flow.

O ideal de exatidão desligado das situações concretas do uso da linguagem carece de qualquer sentido para a abordagem wittgensteiniana, o que a leva a não dispensar toda e qualquer forma de comunicação intersubjetiva, enquanto acordo prévio sobre o uso da linguagem e da interpretação do mundo ligada a ele. Este texto, em suas três partes, busca uma compreensão desse acordo, bem como avalia a possibilidade ou não de a filosofia desempenhar algum papel em relação a ele. Inicialmente, serão considerados os obstáculos a tal acordo, a saber, o solipsismo e a linguagem privada, subjetiva. Na etapa seguinte, procura-se indicar que o rompimento com a concepção subjetivista de linguagem permite a Wittgenstein a visualização de um outro sujeito, o incorporado pela comunidade; a partir daí, procura-se verificar a possibilidade da reflexividade, no âmbito da comunidade linguística, haja vista a objetividade dos conceitos não ser buscada no conhecimento, e sim no interior das formas de vida. Na terceira e última parte, procura-se mostrar a metáfora do jogo de linguagem correlata ao significado que emerge do fluxo da vida, do pensamento, da cultura e como a filosofia pode representar atividade significativa na busca por entendimento desse fluxo.
Agreement, reflectivity and philosophy - an analysis based on Wittgenstein
Keywords: filosofia da linguagem; Wittgenstein; jogos de linguagem; Investigações filosóficas; Tractatus